Happiness and arousal: framing happiness as arousing results in lower happiness ratings for older adults - Bjalkebring, Par (Front Psychol, 2015)
Older adults have been shown to describe their happiness as lower in arousal when compared to younger adults. In addition, older adults prefer low arousal positive emotions over high arousal positive emotions in their daily lives. We experimentally investigated whether or not changing a few words in the description of happiness could influence a person’s rating of their happiness. We randomly assigned 193 participants, aged 22–92 years, to one of three conditions (high arousal, low arousal, or control). In line with previous findings, we found that older participants rated their happiness lower when framed as high in arousal (i.e., ecstatic, to be bursting with positive emotions) and rated their happiness higher when framed as low in arousal (i.e., satisfied, to have a life filled with positive emotions). Younger adults remained uninfluenced by the manipulation. Our study demonstrates that arousal is essential to understanding ratings of happiness, and gives support to the notion that there are age differences in the preference for arousal.